(untitled) (Pedagogical Horizons, 2025)
The article deals with the growing challenges facing liberal democratic systems and the central role of schools and political education in strengthening young people’s democratic awareness. Political education imparts knowledge, critical thinking skills and opportunities for participation, and promotes a democratic school culture. Although political education is firmly established in the Austrian school system, there is a clear gap between theory and practice. Empirical findings show that political topics are rarely covered in class and that teachers find them challenging. Democratic participation in everyday school life is rarely used: class councils and school parliaments are hardly established. The project ‘Democratic Awareness of Young People in Austria’ (2024–2026) uses a nationwide survey of 14- to 15-year-olds to examine their knowledge, attitudes and experiences. Initial results (N=1995) show that only about 10% perceive political education as being strongly present in the subject GPB. Although the importance of diversity of opinion is highly valued, many learn little about forming their own judgements or developing political competence. Young people’s interest in participation and democratic involvement is high, even though they are not yet eligible to vote. The results indicate a need for action: political education must be made more visible in the classroom and more strongly integrated into school structures. In addition to legal and curricular frameworks, teachers need practical training above all. Schools are called upon to consistently enable participation in order to not only teach democracy, but also to bring it to life. In this way, schools can become a central space for experiencing democratic culture and help young people develop political awareness.